Stone matrix asphalt : theory and practice - Blazejowski, Krzysztof (Boca Raton, Fl. : CRC Press, 2010)
'A comprehensive introduction, this book presents the history, materials, requirements, properties, and applications of Stone Matrix Asphalt (SMA). Detailing the requirements and materials for the mix, including asphalt cement, aggregates, and stabilizers, the author discusses design processes and implementation, alternative design methods, and best practices and production processes both in the U.S. and abroad. It covers issues specific to the mix, such as permanent deformation and fatigue resistance, as well as special applications of SMA, including bridge deck surfacing, airfields, and runways. Written in an easy-to-read style, it draws on the author's notable expertise and provides over 400 references'--
Includes bibliographical references and index.
Keywords: Pavements, Asphalt -- Materials; Asphalt rock